Loss-of-Function Variants in HOPS Complex Genes VPS16 and VPS41 Cause Early Onset Dystonia Associated with Lysosomal Abnormalities - Steel, Dora; Zech, Michael; Zhao, Chen; Barwick, Katy E S; Burke, Derek; Demailly, Diane; Kumar, Kishore R; Zorzi, Giovanna; Nardocci, Nardo; Kaiyrzhanov, Rauan; Wagner, Matias; Iuso, Arcangela; et al. (Annals of neurology, 2020)
OBJECTIVES: The majority of people with suspected genetic dystonia remain undiagnosed after maximal investigation, implying that a number of causative genes have not yet been recognized. We aimed to investigate this paucity of diagnoses. METHODS: We undertook weighted burden analysis of whole-exome sequencing (WES) data from 138 individuals with unresolved generalized dystonia of suspected genetic etiology, followed by additional case-finding from international databases, first for the gene implicated by the burden analysis (VPS16), and then for other functionally related genes. Electron microscopy was performed on patient-derived cells. RESULTS: Analysis revealed a significant burden for VPS16 (Fisher's exact test p value, 6.9 × 109 ). VPS16 encodes a subunit of the homotypic fusion and vacuole protein sorting (HOPS) complex, which plays a key role in autophagosome-lysosome fusion. A total of 18 individuals harboring heterozygous loss-of-function VPS16 variants, and one with a microdeletion, were identified. These individuals experienced early onset progressive dystonia with predominant cervical, bulbar, orofacial, and upper limb involvement. Some patients had a more complex phenotype with additional neuropsychiatric and/or developmental comorbidities. We also identified biallelic loss-of-function variants in VPS41, another HOPS-complex encoding gene, in an individual with infantile-onset generalized dystonia. Electron microscopy of patient-derived lymphocytes and fibroblasts from both patients with VPS16 and VPS41 showed vacuolar abnormalities suggestive of impaired lysosomal function. INTERPRETATION: Our study strongly supports a role for HOPS complex dysfunction in the pathogenesis of dystonia, although variants in different subunits display different phenotypic and inheritance characteristics. ANN NEUROL 2020;88:867-877.
Keywords: Dystonia; Exome; Genetic Predisposition to Disease; Vesicular Transport Proteins; Lysosomal Storage Diseases; Male; Middle Aged; mužské pohlaví; rodokmen; exom; osobní újma zaviněná nemocí; genetická variace; mutace; Pedigree; Adult; dystonie; lyzozomální nemoci z ukládání; Genetic Variation; ženské pohlaví; Mutation; Humans; Cost of Illness; Fibroblasts; lidé středního věku; dospělí; genetická predispozice k nemoci; Female; lidé; vezikulární transportní proteiny; fibroblasty